SYNTHESIS AND CHARACTERIZATION OF BISMERCAPTO (2, 2’:6’, 2’’-terpyridine) Ru(II)-COMPLEXES STABILIZED GOLD NANOPARTICLES AND THEIR ELECTRO CATALYTIC REDUCTION OF NITRITE - K. Margandan; M. Jebastin Sonia Jas (Journal of the Chilean Chemical Society, 2018)
Inorganic-organic hybrid structures based on metal-complexes particularly, octahedral bis-2,2’:6’,2’’- terpyridine metal complexes provide an advantages of increased symmetry and in the case of ruthenium(III)/ruthenium(II) complexation an entrance to a directed complexation Method. The Ru (II) terpyridine methane thiolate protected gold nanoparticle was synthesized through covalent bonding of Ru terpyridine methane thiolates over gold nanoparticles surfaces. The ligand terpyridine methanethiolate was synthesized successfully in good percentage of yield. The structures were confirmed and characterized by different physical, analytical, spectral data like FTIR, UV, SEM and Cyclic voltammetry. All the data are shown the expected results.